Consumer Trust in Digital Marketing: A Systematic Literature Review and Conceptual Framework - Hasan, Samsurijal; Mayr, Alexander (Global Insights in Management and Economic Research, 2026)
Purpose of the study: This systematic literature review aims to synthesize existing research on consumer trust in digital marketing contexts, identify key determinants and outcomes of trust, and develop an integrative conceptual framework that advances theoretical understanding and practical applications in digital marketing environments. Materials and methods: A comprehensive systematic literature review was conducted following PRISMA guidelines. Electronic databases including Web of Science, Scopus, ScienceDirect, and EBSCOhost were systematically searched for peer-reviewed articles published between 2014 and 2024. The search protocol utilized keywords: "consumer trust," "digital marketing," "e-commerce trust," "online trust," and "digital consumer behavior." Initial screening yielded 1,847 articles, with 89 studies meeting inclusion criteria after rigorous quality assessment using CASP and JBI critical appraisal tools. Results: The review identified five primary dimensions influencing consumer trust in digital marketing: (1) platform characteristics (security, privacy, design quality), (2) information quality (accuracy, relevance, transparency), (3) social influence (reviews, ratings, social proof), (4) vendor reputation (brand credibility, track record), and (5) technological factors (AI integration, personalization, user experience). Trust significantly impacts purchase intentions (r = 0.67, p < 0.001), brand loyalty (β = 0.58, p < 0.001), and customer engagement. Emerging themes include the dual impact of AI-driven personalization on trust, the critical role of data privacy concerns, and generational differences in trust formation mechanisms. Conclusions: Consumer trust in digital marketing is a multidimensional construct requiring integrated approaches combining technological security, transparent communication, and authentic relationship-building. The proposed conceptual framework integrates cognitive, affective, and behavioral dimensions of trust, providing actionable insights for digital marketers. Future research should examine trust dynamics in emerging technologies (metaverse, blockchain, generative AI) and cross-cultural trust formation patterns.